Increasing motivation through effective homework strategies - Arnold, Craig; Winberry, Kathy (California : Lee Canter & Associates, 1995)
In this program, presenter will address the reasons why students do not complete homework or turn it on time and give practical strategies that can use to increase students' motivation to do homework
Copy available in DVD format
Executive producer, Lee Canter
Narrator: Ron Snow
Host: Lee Canter
Keywords: Homework -- Psychology aspects; Motivation in education; Achievement motivation in children